The Relationship Between Self-Therapy Education for Pregnant Women in Their Third Trimester and Anxiety About Childbirth - Rajia, Rajia; Hermawati, Hermawati; Indang, Wa Ode; Syawal, La Ode Muhamad Irwin; Prety, Fetya (Advances in Healthcare Research, 2025)
Purpose: This study aims to identify the relationship between the Spiritual Emotional Freedom Technique (SEFT) education and anxiety levels in pregnant women in their third trimester. The primary focus is on the effectiveness of SEFT intervention as a non-pharmacological approach in helping to manage anxiety, as well as providing a comprehensive overview of the characteristics of the respondents and changes in anxiety levels before and after the intervention. Research Method: This study used a pre-experimental one-group pretest-posttest design with a sample size of 30 pregnant women in their third trimester. The intervention took the form of structured SEFT education with materials, demonstrations, and guided independent practice by health workers. Data collection included measuring anxiety levels before and after the intervention using standard instruments, which were then analyzed to observe any changes that occurred. Results and Discussion: The results showed a significant decrease in anxiety after SEFT education. Before the intervention, the majority of respondents experienced mild anxiety, while after the intervention, the majority did not experience anxiety. Respondents in the “Good” SEFT education category were mainly in the “No Anxiety” category, supporting the view that targeted education can improve the mental preparedness of pregnant women before childbirth. Implications: This study emphasizes the importance of integrating SEFT education into antenatal care programs as a promotive and preventive strategy. Practically, SEFT can be an easily implemented intervention in primary healthcare facilities at a low cost, yet with a high impact. Recommendations for further research include the use of a control group design, a larger sample size, and a longer observation period to strengthen the validity of the findings.